Epigenetic Regulation of Cytokine Production in Human Amnion and Villous Placenta - Murray D. Mitchell; Anna P. Ponnampalam; Gregory E. Rice (Mediators of Inflammation)
The mechanisms of human preterm labour appear inextricably linked to cytokine biosynthesis by gestational tissues. In turn, cytokine production by gestational tissues has been shown to be regulated by epigenetic mechanisms. In this paper, we demonstrate that cytokine production in gestational tissues is regulated epigenetically in a tissue-specific manner. Furthermore, we show that treatment with a histone deacetylation inhibitor can partially abrogate LPS-stimulated TNFα production in villous placenta but not amnion. LPS treatment significantly (𝑃<0.05) increased the production of IL-1β (~10–34-fold), TNFα (~23–>100-fold) and IL10 (~6–10-fold) after 24 h of treatment in villous explants, as expected. There were no significant LPS effects on IL1Ra production. AZA treatment did not have any significant effect on any cytokines' production tested either alone or in combination with LPS. Interestingly, however, the stimulatory effects of LPS on TNFα production were partially mitigated (𝑃<0.05) by TSA treatment in villous explants. We suggest caution in the consideration of histone deacetylation inhibitors in pregnancy due to the different responses in gestational tissues.